Epidemiology of healthcare-associated SARS-CoV-2 outbreaks in Germany between March 2020 and May 2022. (April 2023) - Suwono, B.; Brandl, M.; Hecht, J.; Eckmanns, T.; Haller, S.
Summary: Background: Outbreaks in healthcare facilities played a pivotal role in the course of the coronavirus (COVID-19) pandemic. Aim: To investigate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreaks in hospitals, outpatient care, and rehabilitation facilities in Germany from March 2020 to May 2022. Methods: Data from the German mandatory notification system were used to describe outbreaks by number of cases and case fatality ratio (CFR), and outbreak cases by age and gender. Using Pearson correlation, the dynamics of cases in the general population were compared with cases in healthcare-associated infection (HAI) SARS-CoV-2 outbreaks before and after the start of the vaccination campaign. Additionally, a counterfactual scenario was used to estimate numbers of prevented HAI cases, using the phase before vaccination as baseline. Findings: By the end of May 2022, 8941 healthcare-associated outbreaks were observed with 73, 626 cases: 51, 504 in hospitals, 15, 524 in outpatient care, and 6598 in rehabilitation facilities. Median number of cases per outbreak was 4 (range: 2–342) and cases were more frequently reported in women with 46, 818 (63.6%). Overall CFR was 8.1%, higher in men (12.4%) than in women (5.7%). After the vaccination campaign was fully introduced, the association between increasing incidence in the general population and consecutive outbreak cases was decreased by a factor of 10. Furthermore, our counterfactual analysis suggests that more than 55, 000 outbreak cases could have been prevented until the end of 2021. Conclusion: The vaccination campaign in combination with non-pharmaceutical measures was key to reduce number, size and CFR of healthcare-associated outbreaks.